Analysis of the Calculation of the Cost of Production Using the Job Order Costing Method for Making Profit Management Decisions at Umkm Putra Berdikari Mojokerto City - Wahyu Solanda Putri; Nersiwad; Rini Armin (CV Putra Publisher, 2023)
The cost of production is one of the important elements in determining the selling price of a product and the profits earned by a company. The calculation of the correct cost of production is very important for company management to assist decision making in setting selling prices and profits. This research is a quantitative descriptive study that aims to determine the calculation of the cost of production of ordered goods using the method applied by UMKM Putra Berdikari, knowing the calculation of the cost of production using the job order costing method at UMKM Putra Berdikari for making profit management decisions, knowing the difference between the calculation of the cost of production production carried out by UMKM Putra Berdikari using the job order costing method. Data collection methods used are interviews, observation, literature study and documentation. The results of this study indicate that there is a difference between the calculation of the cost of production carried out by UMKM Putra Berdikari and the calculation of the cost of production based on the job order costing method. The results of calculating the cost of production carried out by MSMEs are lower than the results of calculating the cost of production based on the job order costing method. This is because the calculation of the cost of production of Putra Berdikari UMKM is still relatively simple, UMKM still has not classified production costs correctly so that the profits obtained are not optimal.